Working towards Sustainable Development : Opportunities for decent work and social inclusion in a green economy. - Office, International Labour (International Labour Office, 2012)
This joint ILO/UNEP study shows that, if accompanied by the right policy mix, a green economy can also create more and better jobs, lift people out of poverty and promote social inclusion. It also demonstrates that employment and social inclusion must be an integral part of any sustainable development strategy. A green economy is necessary if sustainable development is to be realized. However, as this report emphasizes, a green economy can also, if accompanied by the right policy mix, create more and better jobs, lift people out of poverty and promote social inclusion. In fact, the growth mode.